A new species of Arrhopalites Börner, 1906 (Collembola, Symphypleona, Arrhopalitidae) from Iran with an updated key to A. diversus group of species - Vargovitsh, Robert S.; Kahrarian, Morteza (Zootaxa, 2020)
A new springtail species of the family Arrhopalitidae, Arrhopalites persicus sp. nov., is described from Kermanshah Province in Iran. It belongs to the diversus group of species with 3, 2, 1, 1 anterior setae on dens. It is separated from all members of this group by presence of 5+5 circumanal spines on the sixth abdominal segment and it shows reduced tibiotarsal chaetotaxy. It is the second species of the genus recorded in the country. A key to Arrhopalites diversus group of species is updated.